2001
DOI: 10.1183/09031936.01.17100460
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine inhalation challenge: a shorter, cheaper and safe approach

Abstract: Methacholine inhalation challenge: a shorter, cheaper and safe approach. G. Izbicki, E. Bar-Yishay. #ERS Journals Ltd 2001. ABSTRACT: Increased nonspeci®c bronchial hyperresponsiveness to pharmacological agents such as histamine or methacholine (MCh) is a hallmark of asthma. The measurement of airway reactivity is quite sensitive but testing is tedious, and time and money consuming. The present aim was, therefore, to design the shortest possible, yet safe inhalation challenge protocol applicable for a lung fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Two more recent studies evaluated the effectiveness and safety of shorter methacholine challenge protocols. 17,19 Izbicki and BarYishal 17 performed a MCT in a lung function referral center and the initial methacholine concentration was 0.03 mg/mL followed by tripling concentrations up to 8 mg/mL. The authors concluded that an initial concentration of 0.21 mg/mL may be used when the baseline ratio of FEV 1 / FVC is greater or equal to 0.80, and a tripling dose protocol is easier to perform and safe.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Two more recent studies evaluated the effectiveness and safety of shorter methacholine challenge protocols. 17,19 Izbicki and BarYishal 17 performed a MCT in a lung function referral center and the initial methacholine concentration was 0.03 mg/mL followed by tripling concentrations up to 8 mg/mL. The authors concluded that an initial concentration of 0.21 mg/mL may be used when the baseline ratio of FEV 1 / FVC is greater or equal to 0.80, and a tripling dose protocol is easier to perform and safe.…”
Section: Discussionmentioning
confidence: 94%
“…Although abbreviated methacholine protocols are attractive and several alternatives have been examined, the impact of excluding higher concentrations has not been previously evaluated. Several investigators have evaluated the impact of deleting low concentrations, however their focus was on the safety of the test, [15][16][17][18][19] rather than on the measures of responsiveness. Chatham et al 15 compared a full protocol methacholine challenge test, with an abbreviated test in 23 subjects, of which 13 were asthmatics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of children (15 boys, 10 girls) who completed the protocol was 12.2 years (range [8][9][10][11][12][13][14][15][16]. The median age of children (15 boys, 10 girls) who completed the protocol was 12.2 years (range [8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…This procedure has been shown to take from 35 to 65 min. 2,3 There have been numerous efforts to reduce the length of bronchial challenge tests: (1) shortening the length of time between doses, 4 (2) employing threefold or fourfold jumps rather than doubling steps, [3][4][5] or (3) starting the challenge at a higher concentration. 6,7 A direct challenge using histamine at 1-min intervals relies on a cumulative dose to provoke bronchoconstriction 4 ; however, histamine administered at 5-min intervals has been shown to be entirely independent of cumulative dose.…”
mentioning
confidence: 99%